1999
DOI: 10.1002/(sici)1097-0347(199908)21:5<414::aid-hed6>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating cell nuclear antigen and c-erbB-2 oncoprotein expression in adenoid cystic carcinomas of the salivary glands

Abstract: Background Adenoid cystic carcinoma (ACC) of the salivary gland shows a variable clinical course. It would be helpful to discover reliable biologic markers in the management of patients with ACC. Methods We examined proliferating cell nuclear antigen (PCNA) and c‐erbB‐2 oncoprotein expression on 30 cases of ACC of the salivary glands. The immunohistochemical results, and size, location, and histologic grade of the tumors were compared with the clinical outcome of the patients. Results Mean PCNA positivity of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(10 citation statements)
references
References 33 publications
0
9
1
Order By: Relevance
“…Several groups have demonstrated that HER2/neu is overexpressed at both the protein and mRNA levels in SGCs, ACCs, and MECs [28-31]. Further studies have shown that the high HER2/neu expressing patients with ACC have a significantly shorter disease-free interval compared to those with low HER2/neu expression [32]. Moreover, the expression of HER-2/neu is correlated with local disease recurrence, distant disease metastasis, and overall survival of different histological types in SGC patients [33-36].…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have demonstrated that HER2/neu is overexpressed at both the protein and mRNA levels in SGCs, ACCs, and MECs [28-31]. Further studies have shown that the high HER2/neu expressing patients with ACC have a significantly shorter disease-free interval compared to those with low HER2/neu expression [32]. Moreover, the expression of HER-2/neu is correlated with local disease recurrence, distant disease metastasis, and overall survival of different histological types in SGC patients [33-36].…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of some antibodies has been improved with the recent use of antigen retrieval agents for archival, paraffin-embedded tissues (30). Only Cho et al (25) and the present study have used these antigen retrieval agents for ACC, where 17 and 16%, respectively, of HER2/neupositive cases were observed. In the absence of standardized laboratory procedures, it would be hard to compare these figures with similar studies.…”
Section: Discussionmentioning
confidence: 50%
“…During the past decade, ACC of salivary gland origin was also studied for overexpression of HER2/neu (19)(20)(21)(22)(23)(24)(25)(26). Results of the studies varied greatly from no overexpression of HER2/neu (19,20) to 5% (24), 17% (25), over 50% (21,22) and 100% (23,26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations